The Effect of Problem-Based Learning Model on Junior High School Students’ Communication Skills in Earth and Solar System Topic - Rahmi, Auziatul; Fadilah, Muhyiatul; Yanto, Febri; Azhar, Aulia (SEMESTA: Journal of Science Education and Teaching, 2025)
Learning activities in natural science subject have considerable potential for development, particularly in creating a more engaging and communicative classroom environment through active student participation. The implementation of the Problem-Based Learning (PBL) model is expected to enhance students’ communication skills, as it encourages collaborative investigations, problem-solving, and discussion of results. This study aimed to examine the effect of the PBL model on students’ communication skills in learning the Earth and Solar System topic. The research was conducted at SMPN 1 Kec. Guguak over five weeks, from May to June 2024, involving 53 students selected through purposive sampling. The sample consisted of 26 students in the experimental class and 27 in the control class. A quasi-experimental method with a Post-test Only Control Group Design was employed. The indicators of communication skills assessed included oral communication, written communication, and interpersonal communication. Data were collected using a communication test comprising six essay questions that had been validated and tested for reliability. Data analysis was carried out using descriptive statistics and inferential statistics through the Mann-Whitney test with SPSS version 25. The results of the Mann-Whitney test showed a significance value of 0.044 (p < 0.05), indicating that H0 was rejected and Ha was accepted. Therefore, it can be concluded that the PBL model has a significant effect on students’ communication skills.